Anthropometry of the Patellar Tendon in Chinese - KMS Luk (Journal of Orthopaedic Surgery, 2008)
Purpose. To assess the length of the patellar tendon in Chinese and its correlation with patient age, gender, and operated side. Methods. 109 men and 11 women aged 15 to 45 (mean, 25) years underwent arthroscopic bone-tendon-bone reconstruction for anterior cruciate ligament (ACL) insufficiency. 55 (46%) injured the left side, and 65 (54%) the right side. Each patient's age, gender, and operated side were recorded. The length of the patellar tendon harvested was measured. Results. The mean length of the patellar tendon graft was 42.6 (standard deviation, 4.6; range, 30–54) mm. There was no correlation between the length of the patellar tendon and patient's age (p=0.147), gender (p=0.076), or operated side (p=0.466). Conclusion. The length of the patellar tendon in the Chinese is comparable to that in Caucasians. Because of the shorter ACL but similar patellar tendon length, graft-tunnel mismatch may be more common in Chinese than Caucasian patients.